Dai gen. nov., a new genus of Gnaphosinae (Araneae: Gnaphosidae) from Yunnan, China, with descriptions of two new species - Liu, Bo; Zhang, Feng (Zootaxa, 2024)
A new ground spider genus Dai gen. nov. of subfamily Gnaphosinae is described with the type species D. jinchii sp. nov. (♂♀) and D. jijiao sp. nov. (♂) from Yunnan Province, China.